2021
DOI: 10.1007/s11239-021-02526-z
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil activation and circulating neutrophil extracellular traps are increased in venous thromboembolism patients for at least one year after the clinical event

Abstract: Neutrophil activation and neutrophil extracellular traps (NETs) have been associated with the pathogenesis of venous thromboembolism (VTE). Considering VTE-associated chronic sequelae, which suggest that some pathological mechanisms remain after the acute episode, we investigated whether neutrophil activation is increased in patients with a prior VTE at least one year before this investigation. Thirty-seven patients with prior VTE and 37 individuals with no history of VTE were included. Neutrophil activity was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 62 publications
(86 reference statements)
0
3
0
Order By: Relevance
“…Indeed, a higher level of D-dimer was detected in patients recovering from COVID-19, while other coagulation and inflammation markers were at basal levels (237). Besides the aforementioned factors, the assessment of NET markers may also be beneficial in the management of long-term post-COVID-19 patients since it was demonstrated that circulating NET remnants are increased in individuals up to 2 years after the diagnosis of venous thromboembolism (238). Although less is known about the long-term consequences, there is evidence that endothelial activation, low-grade inflammation, and hypercoagulability may persist in post-acute COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a higher level of D-dimer was detected in patients recovering from COVID-19, while other coagulation and inflammation markers were at basal levels (237). Besides the aforementioned factors, the assessment of NET markers may also be beneficial in the management of long-term post-COVID-19 patients since it was demonstrated that circulating NET remnants are increased in individuals up to 2 years after the diagnosis of venous thromboembolism (238). Although less is known about the long-term consequences, there is evidence that endothelial activation, low-grade inflammation, and hypercoagulability may persist in post-acute COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, neutrophils significantly contribute to the development of DVT through their ability to release highly thrombotic NETs [ 44 , 47 , 107 ]. During VTE and for at least 1 year post event, patients exhibit increased levels of activated neutrophils and circulating MPO-DNA complexes [ 108 ]. In mice, depleting neutrophils, administering DNase for the dissolution of NETs or inhibiting the process of NET formation by knocking out Pad4 , have all been associated with DVT protection [ 10 , 44 , 107 , 109 ].…”
Section: Deep Vein Thrombosismentioning
confidence: 99%
“…Endothelial cells directly modulate neutrophil activity through the release of cytokines such as IL-1β, IL-8, and ROS, thereby accelerating the formation of NETs and regulating platelet function ( 104 , 105 ). Meanwhile, NETs activate endothelial cells, promote the production of TXA2 and P-selectin by platelets, activate vascular cell adhesion molecule 1 (VCAM-1) and intracellular adhesion molecule 1 (ICAM-1), facilitate neutrophil migration, and enhance neutrophil-endothelial cell interactions ( 104 , 106 ). One study found that this may be associated with the Gab2 protein (Grb-associated binder to adaptor signaling protein) pathway ( 107 ).…”
Section: Nets Mediate Dvt Formationmentioning
confidence: 99%